Ambiente escolar y su relación con el rendimiento académico de los estudiantes de educación media (2024)
The present research aims to analyze the relationship between the school environment and the academic performance of high school students at the Rural San Antonio educational institution in the city of Sincelejo. The sample includes 32 intentionally selected students who have completed the 10th grade and are continuing to the 11th grade at the school. Additionally, the perception of 2 school administrators and 10 teachers regarding the teacher-student relationship is investigated through interviews. The research adopts a mixed approach comprising descriptive, explanatory, and correlational elements, with a non experimental design within a complementary paradigm. Factors affecting performance, student-student and student-teacher interactions, as well as motivation and attitude during classes, are examined. The results indicate a positive linear relationship between the school environment and students' academic performance. This study contributes to understanding how the school environment influences academic performance and provides valuable insights for improving educational quality